CRITICAL ANALYSIS ON THE IMPACT OF HEALTH CARE REFORM ON THE QUALITY AND COST OF HEALTH CARE SERVICES. - Ali mohammed Abdullah, Mohammed Ahmad Alasseri, Saleh Mohmmed Ali Alyami, Raid Mohammad Abdullah Alajam, Tareq Husain Alqanas, Mahdi Mohammed Ali AAlslom, Hussain Ali Qohsan Alyami,, (Chelonian Research Foundation, 2023)
The reason for actualizing well-being change is to extend the quality and reasonableness of well-being care. This article looks at the effect of these changes on fundamental clinical concepts. Quality change activities, counting the selection of electronic health records (EHRs) and cost-based instalment models, hold a guarantee for making strides in patient results, well-being, and security. Be that as it may, challenges such as gaming behaviour and part administration posture are noteworthy impediments to accomplishing persistent enhancement. Even though a few taken-toll control procedures, such as accountable care organizations (ACOs) and co-payments, have appeared to be able to decrease healthcare investment, concerns remain concerning the general effect of changes and budgeting. This impact analysis the complexities and subtleties of healthcare, giving an understanding of the continuous changes within the healthcare framework and the challenges and openings it faces. Keywords: Health Care Reform, Quality, Cost, Impact Analysis, Healthcare Services